Peningkatan Literasi Digital dan Bahasa Inggris bagi Generasi Muda Desa Kejawang melalui Seminar “AI & English: Kunci Sukses Generasi Masa Depan” - Akhmad Fadjeri; Syafina Hikmah Rahmani; Unggul Priyo Prasojo; Riska Dwi Handayani; Tri Anggoro; Taufik Hidayat; Rissa Filyang; Anisa Dwi Nurchayati; Aulia Rahmawati (Abdibaraya, 2026)
Kejawang Village faces a lack of English language skills and a shortage of competent teachers. One option for addressing this issue is through community service programs and the use of technology.This Independent Community Service Program (KKN) aimed to enhance the understanding of the young generation in Kejawang Village regarding the importance of digital literacy and English proficiency in the globalization era. The method used was an interactive seminar titled "AI & English: Keys to Success for the Future Generation," which was attended by 30 participants from among students and village youth. The seminar material covered a basic introduction to Artificial Intelligence (AI) and motivation regarding the importance of English as a global skill. The results of the activity showed an increase in participants' awareness of the role of AI in daily life and the importance of English for accessing global opportunities. Active participation was evident from the participants' enthusiasm during the Q&A and discussion sessions. The conclusion of this community service is that the seminar successfully served as an initial stimulus in shaping an adaptive, innovative, and competitive young generation. It is recommended that the village government and local educational institutions continue similar programs sustainably to optimize long-term impact